Caffeoylquinic Acid Derivatives Extract of Erigeron multiradiatus Alleviated Acute Myocardial Ischemia Reperfusion Injury in Rats through Inhibiting NF-KappaB and JNK Activations - Zhifeng Zhang; Yuan Liu; Xuecong Ren; Hua Zhou; Kaishun Wang; Hao Zhang; Pei Luo (Mediators of Inflammation)
Erigeron multiradiatus (Lindl.) Benth. has been used in Tibet folk medicine to treat various inflammatory diseases. The aim of this study was to investigate antimyocardial ischemia and reperfusion (I/R) injury effect of caffeoylquinic acids derivatives of E. multiradiatus (AE) in vivo and to explain underling mechanism. AE was prepared using the whole plant of E. multiradiatus and contents of 6 caffeoylquinic acids determined through HPLC analysis. Myocardial I/R was induced by left anterior descending coronary artery occlusion for 30 minutes followed by 24 hours of reperfusion in rats. AE administration (10, 20, and 40 mg/kg) inhibited I/R-induced injury as indicated by decreasing myocardial infarct size, reducing of CK and LDH activities, and preventing ST-segment depression in dose-dependent manner. AE decreased cardiac tissue levels of proinflammatory factors TNF-α and IL-6 and attenuated leukocytes infiltration. AE was further demonstrated to significantly inhibit I-κB degradation, nuclear translocation of p-65 and phosphorylation of JNK. Our results suggested that cardioprotective effect of AE could be due to suppressing myocardial inflammatory response and blocking NF-κB and JNK activation pathway. Thus, caffeoylquinic acids might be the active compounds in E. multiradiatus on myocardial ischemia and be a potential natural drug for treating myocardial I/R injury.